ENVIRONMENTAL ADAPTATION AND SUSTAINABILITY OF BUMDES IN INDONESIA: FUTURE RESEARCH DIRECTIONS AND OPPORTUNITIES - Alifian Rezki Nur Firdhausya; Rudy Suryanto (Jurnal Bisnis dan Akuntansi, 2025)
Over the past decade, research on Village-Owned Enterprises (BUMDes) in Indonesia has grown substantially, yet its contribution to strengthening village economies and institutional practices remains limited. Many studies remain repetitive, focusing on governance, accountability, and performance, while neglecting innovation, paradigm shifts, and broader theoretical development. Research replication without deeper interpretation has led to minimal practical and theoretical contributions. This study addresses the need for a richer research direction by systematically reviewing 19 articles published between 2015 and 2025, each examining strategic issues related to BUMDes in Indonesia. Tranfield’s systematic review methodology maps trends, research gaps, and challenges in BUMDes studies. The analysis identifies three directions for future research: exploration of emerging topical issues, diversification of research paradigms, and application of relevant theories contextualized to the BUMDes setting. These findings underscore moving beyond traditional themes towards more adaptive and innovative approaches. The study is expected to provide a valuable reference for researchers and practitioners in developing research strategies that enhance the role of BUMDes in sustainable village development.